Malignant mesothelioma not related to asbestos exposure: Analytical scanning electron microscopic analysis of 83 cases and comparison with 442 asbestos-related cases. (3rd May 2016) - Kraynie, Alyssa; de Ridder, Gustaaf G.; Sporn, Thomas A.; Pavlisko, Elizabeth N.; Roggli, Victor L.
ABSTRACT: Epidemiological studies indicate that 80–90% of mesotheliomas are asbestos related. This suggests that 10–20% are not. Lung fiber burden analysis provides objective information about past exposures to asbestos. We have performed lung fiber burden analysis on a large cohort of mesothelioma cases and compared the findings with a reference population. Herein we report our findings along with demographic and exposure data.